Biodiversity and Aquatic Vegetation Succession in Biawak Island Marine Protected Area, Indramayu-West Java - Andreas Albertino Hutahaean; Agustin Rustam; August Daulat; Yusmiana Puspitaningsih Rahayu; Devi Dwiyanti Suryono; Hadiwijaya Lesmana Salim; Mariska Astrid Kusumaningtyas (Jurnal Segara, 2022)
The existence of aquatic vegetation in the coastal waters is correlated with the water quality parameters. Seagrass and macroalgae are aquatic plants often found to form a coastal ecosystem that depends on water quality, both physically and chemically. Research on the existence of aquatic plants in Biawak Island, Indramayu, West Java, was conducted in 2016 and 2019 by combining in situ data and secondary data. The purpose of this study was to observe the dynamics of seagrass ecosystems as aquatic plants on Biawak Island and their correlation with the succession that occurred in the aquatic environment in Biawak Island as part of the Biawak Archipelago Marine Protected Area (MPA). The research method integrates a descriptive analysis and its correlation between the submerged aquatic plants and their environment. The results showed that seagrasses in Biawak Island tend to disappear and be replaced by macroalgae. The type of seagrass found in 2016 was Enhalus Acoroides covered by epiphytes perished in 2019. The abundance of macroalgae, especially Halimeda macroloba, indicates the existence of nutrient enrichment and high turbidity, causing the seagrass to be replaced by macroalgae. Another biodiversity found in the region was clams and sea cucumber, while branching coral conditions experienced bleaching and degradation. An environmental condition contains high nutrients strengthening the nutrient enrichment for a particular time. Therefore, integrated management regarding terrestrial and shipping lines track needs to be addressed to maintain the sustainability of the natural resources in the Biawak archipelago.